Reducing harms from treatment. Sixteen years of surgery of the axilla for screen-detected breast cancers in Italy. (December 2018) - Lazzaretti, Maria Grazia; Ponti, Antonio; Mano, Maria Piera; Barca, Alessandra; Casella, Denise; Frigerio, Alfonso; Giordano, Livia; Mantellini, Paola; Paduos, Adriana; Pitarella, Sabina; Ravaioli, Alessandra; Taffurelli, Mario; et al.
Abstract: Objectives: Available evidence on axillary surgery has accumulated dramatically in the last two decades in favor of less invasive care. The aim of this paper is to study 16-years trends in the surgical management of the axilla in a large population-based data set of screen-detected breast cancers in Italy and to document at what extent recommendations have been adopted in actual clinical care. Material and methods: This is a retrospective cohort study documenting the surgical management of the axilla in primary breast cancer patients over time. We retrieved from the Italian database of screen-detected cancers 41213 cases diagnosed in women aged 50–69 between years 2000 and 2015 in twelve Italian Regions. Results: In pN0 cases, an increasing trend (p < 0.001) in the number of patients who received sentinel lymph node biopsy (SLNB) as the only axillary staging procedure was observed. In pN + cases SLNB was the only staging procedure in an increasing number of patients (p < 0.001) especially since the publication of the ACOSOG-Z0011 paper. In ductal carcinoma in situ (DCIS) SLNB was more frequent in mastectomies and in high grade and large lesions. However, 45% of low grade, small DCIS over the whole time period had some form of axillary surgery. Conclusion: This large series of screen-detected cases documents a strong time trend in the direction of reducing axillary surgery and hence potential harms from treatment. The continuing practice of SLNB in low risk DCIS is of concern in an era of increasing awareness towards overdiagnosis and overtreatment. Highlights: Invasiveness of axillary surgery decreased dramatically in the last two decades. Completion ALND in N+ patients decreased since publication of the Z0011 paper. Smaller size, low grade and ER + are inversely associated to completion ALND. Sentinel lymph node biopsy in low risk DCIS shows large variation in use.